2018
DOI: 10.1016/j.eats.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Technique for Superior Capsular Reconstruction Using an Acellular Dermal Allograft

Abstract: Superior capsular reconstruction is a powerful tool for the treatment of massive irreparable rotator cuff tears. Several authors have described this evolving technique. Issues of graft sizing, graft passage, graft tensioning, and suture management make this a challenging procedure even in the hands of experienced shoulder surgeons. We describe our arthroscopic technique for superior capsular reconstruction using nonirradiated human acellular dermis. We introduce several techniques for graft passage and tension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“… 1 , 8 , 13 , 14 , 15 , 16 Nine technical reviews without clinical outcomes were identified by the search. 6 , 7 , 17 , 18 , 19 , 20 , 21 , 22 , 23 One study with clinical outcomes was excluded because the number of patients with each type of graft was not mentioned. 24 The same authors, Mihata et al., 3 , 15 , 25 published 3 papers at 3 different times on the same study population.…”
Section: Resultsmentioning
confidence: 99%
“… 1 , 8 , 13 , 14 , 15 , 16 Nine technical reviews without clinical outcomes were identified by the search. 6 , 7 , 17 , 18 , 19 , 20 , 21 , 22 , 23 One study with clinical outcomes was excluded because the number of patients with each type of graft was not mentioned. 24 The same authors, Mihata et al., 3 , 15 , 25 published 3 papers at 3 different times on the same study population.…”
Section: Resultsmentioning
confidence: 99%
“…Two glenoid anchors can be enough, although if the graft is >35 mm in the anterior-posterior dimension or the distance between the 2 glenoid anchors is >20 mm, a third anchor can be placed in the glenoid without increasing the risk of suprascapular nerve injury. 16,17 Since the original technique of Mihata et al 3 using a fascia lata, different grafts have been described for SCR. Dermal allograft has gained popularity for theitheoretical advantage of reducing donor site morbidity, shorter operative times, and easy preparation, although no clinical studies have confirmed the equivalence of the 2 grafts.…”
Section: Discussionmentioning
confidence: 99%
“…Undertensioned grafts may not restore the superior stability of the glenohumeral joint, and overtensioned grafts may be at increased risk of tearing. 17 Biomechanical studies have investigated the appropriate tension of the graft and suggest that 45 of abduction is the best position to attach the graft, although more studies are required to know the best position for graft fixation and tension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Described posterior-based soft-tissue procedures are fewer but have included simultaneous anterior and posterior reconstruction with Achilles allograft 21 . Recently, an arthroscopic dermal allograft reconstruction procedure was described, 29 which is similar in concept to currently used superior capsular reconstruction techniques 30 …”
Section: Discussionmentioning
confidence: 99%